Cultural Perspective and Approach to Rational Emotive Behavior Therapy in Counseling Post-Disaster Trauma - Suhartiwi; Neviyarni; Yenikarneli; Netrawati (Simposium Antar Bangsa Seminar dan Workshop)
Disasters are sudden events that come from nature, non-nature, and social disasters. Natural disasters, non-natural disasters, and social disasters are very frightening events.Disasters cause damage, destruction, fear, anxiety both physically and psychologically. Disasters bring trauma that is temporary or permanent. This article is to describe disaster management solutions through the Rational Emotive Behavior Therapy (REBT) counseling approach and cultural perspective that will provide a very significant strength in managing post-disaster trauma. REBT invites individuals to always think rationally and reduce irrationality. The Rational Emotive Behavior Therapy (REBT) approach constructs ABC behavior: A (Activating event), B (Belief), and C (Emotional Consequence) change of behavior. REBT is an approach that seesindividuals as part of culture.Individuals experience a process of change personally as the influence of culture in which the influence results in having irrational thoughts.